Curriculum development for Educational Technology based on comparisons of course syllabi resources using lexical analysis - Minoru Nakayama; Katsuaki Suzuki; Chiharu Kogo; Maomi Ueno (European Alliance for Innovation (EAI), 2017)
Current open education resources and the existing online learning environment require appropriate human resources, such as designers and developers, and the technical standards required for these platform to operate and be maintained. Though these resources have been developed at various universities, a standard for course curriculum has not yet been established. To identify content commonly taught in human resource development courses, the interactions between course syllabi at the post graduate level are examined using a combination of lexical analysis and cluster analysis. In the results, some fundamental information and features usable in curriculum for both educational technology and learning technology courses was gathered.